Análise de user experience e user interface em web sites e perfis em serviços de rede sociais online de arquivos estaduais brasileiros - SILVA, Nathália Gomes da (2022)
The objective is to analyze the interfaces available on websites and profiles of Online Social Network Services from Brazilian state archives and apply User Experience and User Interface metrics software, to identify elements of usability and accessibility of the interfaces. As specific objectives, the research proposes i) to present the concepts of User Experience and User Interface; ii) investigate the color models adopted on the websites and profiles of Online Social Networking Services by Brazilian state archives; iii) apply performance tests to the available interfaces, and iv) analyze the test results to verify the current state of compliance with the User Experience and User Interface indicators presented by the performance tests. This research is justified because the websites of Brazilian state archives must be concerned with meeting the indicators pointed out in the User Experience and User Interface analysis techniques, given that the indicators are important points of attention to guarantee the accessibility of the contents of any technological device. In this way, using technical elements that guarantee the accessibility of websites could facilitate access, reducing the complexity of using users.This is an exploratory quantitative and qualitative research carried out through the analysis of the set of home pages of Brazilian state archive websites and their respective official profiles on the Online Social Network Services Facebook, Instagram, and Twitter. The results were divided into four parts: a) Analysis of Lighthouse Indicators - Browser View, b) Analysis of Lighthouse Indicators - Mobile View, c) Analysis of Validator Alerts, d) and Color Palette Analysis. As partial results, it appears that the websites have a dispersion in each analysis, not being possible to define a pattern in the type of challenge faced by the development teams and by the curators of the transmitted information. Regarding the indicators and main errors identified when using the services through the browser, Lighthouse shows that the Performance and Accessibility indices are key factors in the improvement of websites. In addition, the tool also identified the lack of the language definition attribute in the HyperText Markup Language code, which can make it difficult for search engines and other tools to understand the language of the information presented. The results of the Validator tool indicates alerts and errors related to the use of obsolete HyperText Markup Language attributes, errors in attributes related to the representation of the informational content of pages for indexing, errors in the hierarchy of the use of tags in HyperText Markup Language and eXtensible Markup Language, errors in use unnecessary button function in HyperText Markup Language and misuse of HyperText Markup Language structures to represent comments. From the User Interface perspective, it was identified that Online Social Networking Services are responsible for choosing the interface colors, and on websites, there is no standardization in the adoption of color palettes.